Analisis Harga Saham PT. Pertamina Geothermal Energy Tbk Akibat Geopolitik Antara Iran dan Israel - Apni Yunikartika Putri; Sri Auliya Syahrir; Nurul Hikmah; Nur Hishaly GH (Journal of Institution and Sharia Finance, 2024)
This study aims to analyze the difference in Abnormal Return stock price of PT Pertamina Geothermal Energy Tbk by conducting short-term and long-term testing before and after the geopolitics between Iran and Israel and to find out whether there is an impact on the share price of PT Pertamina Geothermal Energy Tbk due to Geopolitics. So the research used is an event study with a quantitative approach. The data analysis technique used is a normality test using kolomogorov testing if the data is normally distributed and hypothesis testing with paired samples t-test testing with a short term of 10 days and a long term of 30 days. The results showed that the short-term and long-term normality tests showed no difference in abnormal returns, while the hypothesis test also showed no difference in abnormal returns. So this shows that there is no difference in the average abnormal return before and after geopolitics and does not affect the share price of PT Pertamina Tbk. Another factor is also the geographical location of Indonesia, Iran, and Israel far from the continent, so the Indonesian stock market is not affected by these events.